Professor Józef Lewandowski - Lewandowska-Gruszka, Bogusława (Archives of Acoustics, 2022)
Professor PhD, DSc Józef Lewandowski, the editor-in-chief of the quarterly Archives of Acoustics (1988–1996) and the deputy editor-in-chief of this journal (1981–1987 and also 1997–2003) died on September 22, 2022. His scientific interests in the field of acoustics were formed during His master’s studies in Physics at the University of Adam Mickiewicz in Poznan (Master’s degree thesis topic: “Limits of audibility of nonlinear distortions of the 2nd, 3rd, 4th and 5th degrees for a pure fifth, including combined tones”).